2019
DOI: 10.31580/jei.v6i3.924
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Performance Based Budgeting and Internal Control Systems on Performance Accountability of Government Agencies: A Case Study In Banjarbaru City Inspectorates

Abstract: The system of good governance is able to realize the governance of the country clean and free from Collusion and Nepotism Corruption (UU 28 year1998). One of the steps of the Banjarbaru City Inspectorates to realize Good Corporate Governance is through the transparency of performance accountability of government agencies  in managing regional finances, most of which are funded by public funds. Performance accountability of government agencies presents budget allocations and realization for implementing key tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
1
2
0
13
Order By: Relevance
“…With regard to financial planning and budgeting practice, studies found that a formal structure of the planning and budgeting process that is supported by good internal control will improve accountability (Kewo, 2014). A similar result was also found in a study by Mujennah et al (2019) where they indicate that the implementation of financial planning and budgeting together with internal control practice monitoring has an influence on accountability. Moreover, controls of firms’ activity under internal control practice are conducted together with financial planning and budgeting to achieve good accountability (Al-Thuneibat et al , 2015).…”
Section: Theory and Hypothesis Developmentsupporting
confidence: 83%
See 1 more Smart Citation
“…With regard to financial planning and budgeting practice, studies found that a formal structure of the planning and budgeting process that is supported by good internal control will improve accountability (Kewo, 2014). A similar result was also found in a study by Mujennah et al (2019) where they indicate that the implementation of financial planning and budgeting together with internal control practice monitoring has an influence on accountability. Moreover, controls of firms’ activity under internal control practice are conducted together with financial planning and budgeting to achieve good accountability (Al-Thuneibat et al , 2015).…”
Section: Theory and Hypothesis Developmentsupporting
confidence: 83%
“…Therefore, associating these two practices with internal control will be able to contribute to good accountability. Besides, the finding also proved that the reliability of financial disclosure and financial performance information depends on effective internal control practice (Mujennah et al, 2019;Pamungkas et al, 2019). It means that internal control is seen to become the most crucial financial management component to be adopted in Malaysian ISEs.…”
Section: Financial Management Practicesmentioning
confidence: 82%
“…Selain dapat mengelola dan melakukan penilaian terhadap risiko perusahaan harus dapat menetapkan mekanisme untuk mengidentifikasi, menganalisis dan mengelola risiko tersebut dengan baik. Penelitian (Mujennah, Artinah, & Safriansyah, 2019) menyatakan bahwa penilaian risiko tidak berpengaruh terhadap AKIP, dari hasil penelitian tersebut peneliti mengajukan hipotesis sebagai berikut : H6 : Penilaian Risiko Berpengaruh Positif Terhadap AKIP Pengaruh Kegiatan Pengendalian Terhadap AKIP (Arens, 2011) membagi kegiatan pengendalian kedalam lima kelompok yaitu: Pemisahan tugas yang jelas, otorisasi yang pantas atas transaksi dan aktivitas, dokumen dan catatan yang memadai, pengecekan independen atas pelaksanaan, pengendalian fisik atas aktiva dan catatan. Kegiatan Pengendalian Intern, yaitu kebijakan dan prosedur yang dapat membantu memastikan dilaksanakannya arahan pimpinan Instansi.…”
Section: Pengaruh Penilaian Risiko Terhadap Akipunclassified
“…Kegiatan Pengendalian Intern, yaitu kebijakan dan prosedur yang dapat membantu memastikan dilaksanakannya arahan pimpinan Instansi. Berdasarkan penelitian (Mujennah, Artinah, & Safriansyah, 2019) menyatakan bahwa kegiatan pengendalian berpengaruh terhadap AKIP, dari hasil penelitian tersebut peneliti mengajukan hipotesis sebagai berikut : H7 : Kegiatan Pengendalian Berpengaruh Positif Terhadap AKIP…”
Section: Pengaruh Penilaian Risiko Terhadap Akipunclassified
See 1 more Smart Citation